Heritage as an Asset in Building Place Brand Identity in Cultural Tourism Business – Proceedings of the Heritage, Tourism and Hospitality International Conference HTHIC 2014 November 6-8, 2014 Istanbul, Turkey - Arja Lemmetyinen; Lenita Nieminen; Liisa Marjoniemi (Boğaziçi University Istanbul, 2022)
Heritage as an Asset in Building Place Brand Identity in Cultural Tourism Business
Heritage is defined as something that we inherit from the past and use in the present day. Heritage can be seen as a carrier of historical values, and therefore viewed as part of the cultural tradition of a society (Nuryanti, 1996; Timothy and Boyd, 2003:4). Recently, traditional heritage research has met a paradigm shift from tangible focus towards more intangible heritage (Richards, 2011). In this paper we argue that the cultural heritage of a place may have an impact on how entrepreneurs in cultural tourism business commit to the joint brand. The efforts of private entrepreneurs have been emphasized to be at the core of successful place branding (Vuorinen & Vos, 2013; Mittilä & Lepistö, 2013; Lemmetyinen & Go, 2010).
This paper concentrates specifically on one particular context: a rural municipality in Finland. In recent years, attempts have been made to attract new visitors, tourist and residents to the area. The municipality has also launched a development project that aims to strengthen the brand building by harnessing the cultural heritage of the area. We used ethnographic techniques with open interviews to explore entrepreneurs’ views on how the heritage of the place is represented and connected to their business. By drawing on Wenger’s (1998) framework of a community of practice, we aim to understand how entrepreneurs experience their attachment to a community and interpret how they commit to a joint brand identity.
Our findings show that in the process of building a joint place brand, the joint values of those involved have to be agreed on. The identity building process can be challenging for artist entrepreneurs. The active role of entrepreneurs in place branding needs to be emphasized. As a practical implication, we found that those responsible for the place branding activities need to be aware of how entrepreneurs belong to a community of practice.
Heritage is defined as something that we inherit from the past and use in the present day. Heritage can be seen as a carrier of historical values, and therefore viewed as part of the cultural tradition of a society (Nuryanti, 1996; Timothy and Boyd, 2003:4). Recently, traditional heritage research has met a paradigm shift from tangible focus towards more intangible heritage (Richards, 2011). In this paper we argue that the cultural heritage of a place may have an impact on how entrepreneurs in cultural tourism business commit to the joint brand. The efforts of private entrepreneurs have been emphasized to be at the core of successful place branding (Vuorinen & Vos, 2013; Mittilä & Lepistö, 2013; Lemmetyinen & Go, 2010).
This paper concentrates specifically on one particular context: a rural municipality in Finland. In recent years, attempts have been made to attract new visitors, tourist and residents to the area. The municipality has also launched a development project that aims to strengthen the brand building by harnessing the cultural heritage of the area. We used ethnographic techniques with open interviews to explore entrepreneurs’ views on how the heritage of the place is represented and connected to their business. By drawing on Wenger’s (1998) framework of a community of practice, we aim to understand how entrepreneurs experience their attachment to a community and interpret how they commit to a joint brand identity.
Our findings show that in the process of building a joint place brand, the joint values of those involved have to be agreed on. The identity building process can be challenging for artist entrepreneurs. The active role of entrepreneurs in place branding needs to be emphasized. As a practical implication, we found that those responsible for the place branding activities need to be aware of how entrepreneurs belong to a community of practice.
Proceedings of the Heritage, Tourism and Hospitality International Conference HTHIC 2014